PENTINGNYA PENDIDIKAN MULTIKULTURAL DALAM MEMBANGUN TOLERANSI DI LINGKUNGAN SEKOLAH - Waldiki Taba; Hermin Rara; Hesli Bulawan; Elsi Kurapak; Sepri Arrang (CV. ADIBA AISHA AMIRA, 2025)
Tolerant, fair, and respectful of diversity. This article aims to examine the concepts, basic principles, implementation strategies, and challenges and solutions in implementing multicultural education in schools. Using a descriptive qualitative approach, this article highlights how multicultural education can be an effective means of building mutual respect in a pluralistic society. The study results indicate that integrating multicultural values into the curriculum, teacher training, and an inclusive school culture are key strategies that must be implemented. However, obstacles remain, such as limited teacher understanding, a lack of teaching materials, and social resistance. Therefore, progressive education policies and the support of all stakeholders are needed for optimal implementation of multicultural education.